Factor Structure and Psychometric Properties of the Stressor Scale in Inclusive Education in Nursery School Teachers of Children With Special Needs in Japan: The Relationship Between Assertiveness and Stress - Shiratori, Mami; Kojima, Michio (Frontiers in Education, 2022)
Due to increases in the number of children with special needs and the demands on nursery school teachers in Japan, the problem of staff burnout has been observed. In this study, we developed the Stressor Scale in Inclusive Education (SSIE) with nursery school teachers of children with special needs and clarified the relationship with childcare experiences of children with special needs. The results showed that nursery school teachers currently in charge of children with special needs or who had overseen children with special needs were significantly more likely to report experiencing stressors in the SSIE subscale “Human relations with parents and other children in the class” than those who had not overseen children with special needs. In addition, the Japanese version of the Rathus assertiveness schedule (J-RAS), developed by Rathus, was used to examine the relationship between assertiveness and stress in nursery school teachers and revealed a negative relationship between the SSIE subscale “Insufficient self-expertise” and J-RAS scores. Therefore, to reduce the stressors among nursery school teachers, nursery school teachers should have a sense of their expertise.